Today's business communication : a how-to guide for the modern professional - Snyder, Jason L.; Forbus, Robert (2013 digital library., 2014)
This handy guide to excellent business communications is perfect for both college students and business professionals. Whether preparing for a career, launching a career, or advancing in a career, the savvy professional understands that every organization expects employees to be exceptional business communicators. Today's Business Communication: A How-to Guide for the Modern Professional leads readers through the most frequently encountered business communication situations. Two business partners who are also business school professors share their combined 30 years of marketing and communication experience with readers in this accessible, entertaining, and informative guide. The authors enhance the readers' experience through anecdotes from business professionals from different industries.